A reconstrução da fé no enfrentamento do luto : teologia e psicologia em diálogo - Costa, Ana Paula Reis da (2015)
This research aims at a dialogue between Theology and Psychology in order to understand the Catholic faith and their possible mobilization within the psychic processo of assimilation and elaboration of mourning, using the clinical history of two Catholic bereaved patients followed up in psychoterapy in their first years of bereavement as a concrete object of analysis in a longitudinal study. The Project is part of a historical and philosophical literature on death and then supplies from the contribuitions of Jurgen Moltmann in the Theology of Hope, the psychoanalyst John Bowlby s productions and his sucessor, the psychiatrist Colin Parkes on data about the mourning and recovery. Conclusively, from the analysis of the theological content found, it was established that the fight arouses intense and profound theological transformation process that reached three categories: faith, God and the Communion of Saints,causing changes that potentially infer the recovery conditions of the bereaved, as well as their way of being and living after the loss, pointing to the need for a differentiated listening to the data found on faith, against human care in bereavement.